2004
DOI: 10.4314/eamj.v81i1.8795
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia, urinary tract infection and malaria in hospitalised febrile children in Nairobi: is there an association?

Abstract: Background: There is laboratory evidence of altered immune function in children with malaria. Bacterial infections have been documented to complicate severe forms of malaria. However, it remains unclear whether such infections are attributable to the malaria, other risk factors, or are coincidental. Objective: To determine the prevalence of bacteraemia and urinary tract infections (UTI) in febrile hospitalised children with and without malaria. Design: A cross-sectional survey. Setting: General paediatric ward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 19 publications
3
47
2
Order By: Relevance
“…The current study, in contrast to earlier studies (Akpede and Skyes, 1992;Okwara et al, 2004) observed a significant association between parasite density and bacteriuria. This could be attributed to the high prevalence of malaria, and the relatively younger age of participants recruited in this study.…”
Section: Figure 1: Prevalence Of Bacteria Isolate Stratified By Agecontrasting
confidence: 99%
See 3 more Smart Citations
“…The current study, in contrast to earlier studies (Akpede and Skyes, 1992;Okwara et al, 2004) observed a significant association between parasite density and bacteriuria. This could be attributed to the high prevalence of malaria, and the relatively younger age of participants recruited in this study.…”
Section: Figure 1: Prevalence Of Bacteria Isolate Stratified By Agecontrasting
confidence: 99%
“…Earlier works by Osegbe et al,(1991), Musa-Asien et al, (2003) and Okwara et al, (2004) reported E. coli as the predominant isolate. However, in agreement with the work of Okunola et al, (2012) Staphylococcus aureus was identified as the main isolate among children in the Assin South Municipality.…”
Section: Figure 1: Prevalence Of Bacteria Isolate Stratified By Agementioning
confidence: 81%
See 2 more Smart Citations
“…and R. felis were detected at high levels, mostly during the rainy season and among children <15 years of age (Figure 2), but no coincidental relationship was found. The incidence of co-infection of R. felis and malaria was lower in Senegal (23%) than in Kenya (79%) ( 5 ), but higher than the rate of simultaneous bacterial bloodstream infections and malaria parasitemia, which ranged from 6% in rural Mozambique ( 23 ) to 11% in Nairobi ( 24 ). Mixed infections for rickettsioses, including co-infections with malaria or with other bacteria ( Leptospira spp., Coxiella burnetii , and Burkholderia pseudomallei ) have been described ( 25 ).…”
Section: Discussionmentioning
confidence: 92%